2014
DOI: 10.4269/ajtmh.13-0161
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Susceptibility to Japanese Encephalitis Virus in Domestic Ducklings and Chicks

Abstract: Abstract. Ardeid birds and pigs are known as major amplifying hosts for Japanese encephalitis virus, and ducklings and chickens have been considered to play at best a minor role in outbreaks because of their low or absent viremia. We hypothesized that viremia of sufficient magnitude would develop in young ducklings (Anas platyrhynchos) and chicks (Gallus gallus) for them to serve as reservoir hosts and thereby contribute to the transmission cycle. Infection was associated with reduced weight gain in both speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 24 publications
2
81
0
Order By: Relevance
“…This difference may translate a different combination of hosts, vectors and agricultural practices in the two areas, pointing out the importance of taking into account these parameters when planning control programs [17]. In the absence of wild waterbirds in periurban and urban areas, domestic and peridomestic species such as passerine birds may play a role in the transmission and the maintenance of the virus as suggested by the JEV viremia experimentally observed in poultry [15] and in several native North American passerine species [16]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference may translate a different combination of hosts, vectors and agricultural practices in the two areas, pointing out the importance of taking into account these parameters when planning control programs [17]. In the absence of wild waterbirds in periurban and urban areas, domestic and peridomestic species such as passerine birds may play a role in the transmission and the maintenance of the virus as suggested by the JEV viremia experimentally observed in poultry [15] and in several native North American passerine species [16]. …”
Section: Discussionmentioning
confidence: 99%
“…The main vectors such as Culex tritaeniorhynchus breed mostly in rural settings, however, other species like Culex quinquefasciatus , an anthropophilic species, could play an a role in JE transmission in periurban or urban areas [12,13]. Beyond the aquatic wild birds traditionally suspected to be the main reservoir [5,14], several host species are also thought to be able to play a role in the transmission of the virus such as poultry or non-aquatic wild birds such as passerine birds that experimentally show sufficient viremia to allow virus transmission [1517]. This means that JE could be transmitted and even maintained in a wide range of environments beyond the typical rural, paddy-fields dominated landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental subcutaneous infection of ducklings and chicken with JEV has shown that youngest animals were more susceptible to the infection than older animals and that the mean peak viremia in birds of both species decreased as the age at infection increased from 2 to 42 days, suggesting that young poultry may be amplifying hosts of importance in disease‐endemic regions (Cleton, Bosco‐Lauth, Page, & Bowen, ). In our study, young birds resulted infected by JEV were younger than 2 months and thus they were born probably when episodes of bird mortality occurred in Tuscany.…”
Section: Discussionmentioning
confidence: 99%
“…cattle egrets and pond herons) act as important natural reservoirs as well as maintenance hosts for JEV and may also be responsible for the spread of JEV in virgin soil (Upadhyay & Ahmad, 2011). Adult ducks and chickens are also susceptible to infection with JEV with low viremia but unlikely to substantial transmission to feeding mosquitoes (Cleton et al, 2014). However, hatched chicks might develop much higher viremia than adult birds which suggests their minor role in JEV transmission in endemic regions.…”
Section: Transmissionmentioning
confidence: 99%